Self-Concept as a Mediator of the Relation Between University Students’ Resilience and Academic Achievement - García-Martínez, Inmaculada; Augusto-Landa, José María; Quijano-López, Rocío; León, Samuel P. (Frontiers in Psychology, 2022)
Academic achievement is a factor of interest in both psychology and education. Determining which factors have a negative or positive influence on academic performance has produced different investigations. The present study focuses on analyzing the relationship between resilience, emotional intelligence, self-concept and the academic achievement of university students. For this purpose, different self-report tools were administered to a sample of 1,020 university students from Southern Spain. The Structural Equation-based mediational analysis suggests that there is no direct relationship between resilience and academic achievement, nor between emotional intelligence and academic achievement. Likewise, self-concept is positioned as a mediating factor in the relationship between resilience and academic achievement. The findings indicate that university students who exhibit high levels of resilience tend to cope better with difficult moments and understand and value the effort required and invested in study time. This study supports positive beliefs and behaviors for better academic achievement.